Step by Step to Substance Abuse Prevention. The Planning Guide for School-Based Programs - Fetro, Joyce V. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1991)
This planning guide defines the steps for creating an effective substance use prevention program for kindergarten through grade 12 (K-12). It is written for administrators, health educators, counselors, social workers, and any other professionals involved with planning and implementing school-based programs and services. Chapter 1 summarizes up-to-date research about alcohol, tobacco and other drug problems as well as factors influencing drug use among youth. It explains how this research can be used to plan and implement programs. Chapter 2 offers an overview of prevention, identification, and intervention strategies that can be used in school-based programs. A comprehensive model for making linkages in programs and services is described. Attention is given to the essential area of establishing partnerships among schools and community agencies. Chapter 3 provides a framework that uses a step-by-step planning approach with worksheets for assessing existing services and programs, identifying and prioritizing gaps, and developing program and evaluation activities. Throughout the guide, practical tools in the form of checklists assist readers in actually doing the planning. Visual aids such as figures and tables summarize and highlight key concepts facts and processes. More than half of the document is devoted to appended worksheets, the Youth Risk Behavior Survey, and a description of drug prevention curricula content areas. (LLL)
Availability: Network Publications, 1700 Mission St., Suite 203, P.O. Box 1830, Santa Cruz, CA 95061-1830 ($19.95).
Educational level discussed: Elementary Secondary Education.
Educational level discussed: Kindergarten.
Practitioners.
Microfiche.
Keywords: Community Education; Crisis Intervention; Curriculum Development; Drug Use; Elementary School Students; Elementary Secondary Education; Family Counseling; Fund Raising; Health Education; Identification; Individual Counseling; Inservice Teacher Education; Kindergarten; Preschool Children; Prevention; Program Development; Program Evaluation; Referral; Risk; School Health Services; Secondary School Students; Substance Abuse; Guides, General